2006
DOI: 10.1016/j.devcel.2006.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Inhibitors Regulate the Transcriptional Response to Morphogenetic Shh-Gli Signaling in the Neural Tube

Abstract: Shh-Gli signaling controls cell fates in the developing ventral neural tube by regulating the patterned expression of transcription factors in neural progenitors. However, the molecular mechanisms that limit target gene responses to specific domains are unclear. Here, we show that Wnt pathway inhibitors regulate the threshold response of a ventral Shh target gene, Nkx2.2, to establish its restricted expression in the ventral spinal cord. Identification and characterization of an Nkx2.2 enhancer reveals that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 46 publications
8
123
1
1
Order By: Relevance
“…To examine the direct regulatory actions of the Shh-initiated transcriptional network (Lei et al, 2006;Oosterveen et al, 2012;Peterson et al, 2012), we performed ChIP-seq for Nkx2.2, Nkx6.1 and Olig2 on neural progenitors derived in vitro from mouse embryonic stem cells (mESCs); a model system that recapitulates in vivo patterning processes (Peterson et al, 2012;Wichterle et al, 2002) (supplementary material Table S1). The binding events were reproducibly detected in biological replicates (supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To examine the direct regulatory actions of the Shh-initiated transcriptional network (Lei et al, 2006;Oosterveen et al, 2012;Peterson et al, 2012), we performed ChIP-seq for Nkx2.2, Nkx6.1 and Olig2 on neural progenitors derived in vitro from mouse embryonic stem cells (mESCs); a model system that recapitulates in vivo patterning processes (Peterson et al, 2012;Wichterle et al, 2002) (supplementary material Table S1). The binding events were reproducibly detected in biological replicates (supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed analyses showed that a number of known neural fate determinants as well as components of the Hedgehog pathway were co-targeted ( Fig. 1E,F (Lei et al, 2006;Oosterveen et al, 2012;Peterson et al, 2012;Wang et al, 2011), intersectional analysis showed a limited overlap with Gli1-and Gli3-bound regions overall ( Fig. 1G; supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments in Drosophila have shown that Wnt and Shh interactions occur in the embryonic epidermis and in the larval leg imaginal disk (31,32). In the developing vertebrate spinal cord, interactions have been reported between Shh and Wnt signaling pathways in regulating patterning and cell specifications (32,33). In mammalian systems, Lef1 null mice had been observed to have reduced expression of Shh in the developing tooth germ (34), and ␤-catenin mutant mice showed reduced Shh expression in hair follicles (35).…”
Section: Discussionmentioning
confidence: 99%